Ways of increase of tolerance of, and adherence to antibacterial therapy - A. V. Vorontsova; M. A. Zvychainy; K. G. Zvereva; E. F. Chaus; D. V. Vysotskaya; R. A. Gabbasova; G. T. Karanaeva (Лечащий Врач, 2021)
The use of certain ABs is accompanied by the development of AAD (not only during the administration of drugs, but also within 2 months after its completion), which reduces the compliance rate of the treatment and increases the frequency of violation of the schedule of AB drugs and can negatively affect the effectiveness of the prescribed therapy. The preventive use of butyric acid and inulin together with AB can reduce the relative risk of developing AAD and increase the compliance of the treatment; and due to these effects, it is possible to increase the frequency of elimination of pathogenic and conditionally pathogenic microorganisms in the treatment of inflammatory infectious diseases and reduce the likelihood of developing antibiotic resistance.